Historical Perspectives and Memories of Progressive Supranuclear Palsy - Steele, John C. (Seminars in Neurology, 2014)
Parkinsonism recalls James Parkinson of London and his description of six patients with “paralysis agitans” in 1817, which neurologist Jean-Marie Charcot renamed Parkinson disease. Its variants, referred to as atypical parkinsonian disorders, are the subject of this issue of Seminars in Neurology through which we continue a journey toward understanding the pathogenesis of these diverse neurodegenerative diseases that are sometimes genetically determined, but are more often sporadic and without familial occurrence.
Keywords: progressive supranuclear palsy; tauopathy; amyotrophic lateral sclerosis/parkinsonism dementia complex; prion